Elevated Expression of KiSS-1 in Placenta of Chinese Women with Early-Onset Preeclampsia - Qiao, Chong; Wang, Chunhui; Zhao, Jiao; Liu, Caixia; Shang, Tao (PLOS ONE, 2012)
Preeclampsia (PE) is a heterogeneous syndrome affecting 2% to 8% of all pregnancies and is the world’s leading cause of fetal and maternal morbidity and mortality. In many cases of PE, shallow trophoblast invasion results in inappropriate maternal spiral artery remodeling and impaired placental function. Multiple genes have been implicated in trophoblast invasion, among which are KiSS-1 and GPR54. The gene product of KiSS-1 is metastin, which is a ligand for the receptor GPR54. Both metastin and GPR54 are expressed in the placenta of normal pregnancy and have been implicated in modulating trophoblast invasion through inhibiting migration of trophoblast cells. We have previously reported that the expression level of KiSS-1 was higher in trophoblasts from women with preeclampsia as compared to normal controls. Here, using quantitative RT-PCR, Western blot analysis and immunohistochemistry, we extend our analysis to demonstrate that elevated KiSS-1 expression occurs only in early-onset preeclampsia (ePE) and not late-onset preeclampsia (lPE). However, no difference in the expression levels of GPR54 is observed between ePE, lPE, and normal controls. Further, we show that KiSS-1 expression is also increased in placenta of intrauterine death and birth asphyxia in comparison to normal newborns of ePE and lPE. Our findings suggest that aberrant upregulation of KiSS-1 expression may contribute to the underlying mechanism of ePE as well as birth asphyxia.